Waste materials composited into an adsorbent for landfill leachate treatment - K. K. P. S. Kumara; W. K. C. Neetha Dayanthi (IWA Publishing, 2023)
The ability of a composite adsorbent composed primarily of various waste materials to adsorb heavy metals, NH3-N, and chemical oxygen demand (COD) from landfill leachate was investigated through batch sorption experiments. The study determined the optimal contact time and adsorbent dosage for the removal of Pb, Zn, Cu, Fe, NH3-N, and COD to be 15, 90, 30, 180, 30, and 30 min, respectively. The corresponding optimum adsorbent dosages were determined to be 5, 30, 5, 15, 5, and 30 g, respectively. The composite adsorbent exhibited high removal efficiencies, achieving the following maximum values: 96.4% for Pb, 92.7% for Zn, 60.3% for Cu, 87.1% for Fe, 75.0% for NH3-N, and 67.5% for COD. Pb and Fe showed the best fit with a Langmuir isotherm model, with corresponding adsorption capacities of 0.0165 and 1.14 mg/g, respectively. For Zn, Cu, NH3-N, and COD, the equilibrium data demonstrated the best fit with an Elovich isotherm model, with adsorption capacities of 0.004, 0.005, 0.016, and 4.29 mg/g, respectively. The kinetic data followed the pseudo-second-order kinetic model. It presented a potential solution for the disposal of the waste from which it was derived. HIGHLIGHTS This investigates the applicability of a composite adsorbent made of low-cost/waste materials, in landfill leachate treatment.; The composite adsorbent has considerable treatment potential.; This can be an initial study leading to further studies.; The use of waste materials makes treatment economically and practically feasible.; This is also a sustainable reuse application for the waste to be dumped.;